Epigenetik Implikationen für die Lebens- und Geisteswissenschaften - Walter, Jörn (Nomos Verlagsgesellschaft mbH & Co. KG, 2017)
Do the mechanisms of epigenetics control our genes? Or maybe not? The field of epigenetics investigates the complex molecular interaction of genes and their physical environment. Epigenetic mechanisms can alter our DNA structurally, change gene expression and thus drive cellular development throughout life. They have currently been associated with numerous diseases and are known to shape both appearance and behavioral patterns. Environmental factors as well as lifestyle choices come into play and impart their